The Criterion of Ethical Rules in the Islamic Political System - s.fateme faghihi (اخلاق وحیانی, 2016)
The aim of this paper is to investigate the basis and criterion of ethical values in Islamic political system. The implementation of ethical rules in a political system requires a knowledge of its ethical criterion. There are four approaches for explaining the criterion of ethical rules: deontologism, consequentialism, virtue ethics, and truth-orientedness. All of these ethical approaches try to answer the question of what is the criterion for an ethical action to be valuable. Because of the diversity of ethical theories, even in the Islamic ethics, it is crucial to determine which criterion and approach is the basis of ethical, political actions. Investigation the ethical approaches and the political effects of each one of them, I believe that the diversity of ethical approaches is a consequence of one-dimensional, extremist view on one of the aspects of ethical action. It is while the governing ethical theory of a political society must be a comprehensive approach that consider each ethical approach in a certain level and with respect to its position in the ethical theory. The ethical approach in the political system of Islam has different dimensions and levels that each of them has a certain function and status, and the ethical system doesn’t lead to any consequence alone. So, looking for solution doesn’t have any conflict with deontologism and virtue ethics, and extremism in any level would lead to carelessness about other levels and emergence of inefficient ethical theory.